Quest for Mutual School-Community Relationship In Nigeria: The Critical Centrifugal Forces - Ige Akindele Matthew (Jurnal Educative: Journal of Educational Studies, 2020)
Mutual school-community relationship is imperative in the educational system due to the associated benefits. One of the purposes of establishing a school is to serve the immediate community. A community also needs to monitor and supervise the schools located within it, attend to their needs, challenges, as well as monitor their progress, so that there will be effective management of the schools while the set objectives can be achieved.  In this paper, critical forces pulling schools and communities apart (i.e. centrifugal forces) in Nigeria, such as theft of school properties, encroachment into school’s land/territory, interference in school’s activities, invasion of school by hoodlums, ritual killings, and obstruction of movement of staff, indiscipline of pupils/students and teachers,  as well as the apathy of school to community’s activities, are examined. To tackle the forces and achieve mutual school-community relationships, all hands must be on deck, particularly, by the parties to the school and community relationship. In this case, non-apathy of school to community activities, prevention of theft of school properties, non-interference of community members in school affairs, non-interference of parents and community in school affairs, among others, are recommendedHubungan antara sekolah dan masyarakat sangat penting dalam sistem pendidikan karena manfaat yang ada di dalamnya. Salah satu tujuan pendirian sekolah adalah untuk melayani masyarakat yang berada di sekitarnya. Masyarakat juga perlu memantau dan mengawasi sekolah-sekolah yang berada disekelilingnya, memperhatikan kebutuhan mereka, tantangan, serta memantau kemajuan mereka, sehingga akan tercipta manajemen sekolah yang efektif sementara tujuan yang ditetapkan juga dapat tercapai. Tulisan ini menganalisa kekuatan kritis yang  memisahkan antara sekolah dan masyarakat (yaitu kekuatan sentrifugal) di Nigeria, seperti pencurian properti sekolah, gangguan lingkungan sekolah, campur tangan dalam kegiatan sekolah, invasi sekolah oleh preman, ritual pembunuhan, gangguan akan aktivitas staf sekolah, ketidakdisiplinan siswa dan guru, serta sikap apatis sekolah terhadap kegiatan masyarakat. Untuk mengatasi kekuatan tersebut dan mencapai hubungan timbal balik sekolah-masyarakat, semua pihak harus bersinergi, terutama pihak-pihak sekolah dan hubungan dalam masyarakat. Sebagai solusi, ada beberapa kegiatan yang direkomendasikan, diantaranya tidak apatisnya sekolah akan kegiatan masyarakat, pencegahan pencurian properti sekolah, tidak adanya campur tangan anggota masyarakat dalam urusan sekolah, tidak adanya campur tangan orang tua dan masyarakat dalam urusan sekolah